Good Sports, drinking cultures and hegemonic masculinities in a community sporting club case study. (3rd July 2016) - Hart, Aaron
Abstract: Despite the predominantly masculine nature of drinking cultures within Australian community sporting clubs, masculinities have received little attention in the associated research and policy arenas. Focusing on the Good Sports Program, which is designed to change the drinking culture of sporting clubs, this article presents a case study of drinking cultures in a football club. My analysis of interview and field observation material traces interrelations between Program interventions, demographic and social changes, gender hierarchies, drinking settings and norms governing alcohol consumption within the club. I demonstrate that the changes in the drinking culture of the clubrooms have occurred, and that the Good Sports Program played a role in this change. However, "bad behaviour", "drink" and "trouble" remain features of other club settings. I conclude that opportunities exist for further engagements with masculinities, and the socio-material networks that hold them in place, and that these engagements might open the way for more significant changes in the drinking cultures of male sporting clubs.